The Wardrobe Goods of Anna of Denmark, Queen Consort of Scotland and England (1574–1619). (March 2017) - Field, Jemma
Abstract : This article analyses and transcribes an inventory of the wardrobe goods of Anna of Denmark, queen consort of Scotland and England, which was compiled in 1608, and annotated up to and including 1611. The inventory reveals the types of goods that Anna owned, the movement of garments between residences, her involvement in the politicized custom of gift exchange and the concept of her appearance as a point of diplomacy. Arguing that Anna's visual appearance was considered and strategic, it further discredits her narrow and largely negative historiography, which has routinely cast her as a recklessly indulgent and fanciful queen. Anna's tactical visual emulation of Queen Elizabeth I (1533–1603), pointed use of recognizable pieces of inherited jewellery and politically significant colours of dress are discussed.